Design and Implementation of the Balanced Scorecard (BSC) to Improve Business Management in a Lima-based Company that Manufactures Ink for the Graphic Sector - Peralta Loayza, Hector (2022)
This article presents the research conducted in a small-size Peruvian enterprise with economic, financial and sustainability problems. The balanced scorecard (BSC) was designed and implemented in the company under study as a new business management model. To this end, an internal and external analysis of the company was carried out; the vision, values, objectives and strategic indicators were established; and the owners and collaborators were involved in the implementation of the strategic initiatives. The results obtained from the design and implementation of the BSC showed that sales increased and the profit margin improved compared to the same period of the previous year.